Magnetic carrier, manufacturing method of magnetic carrier, two-component developer, and replenishment developer
A magnetic carrier with a polyrotaxane-filled resin core addresses excessive charging issues in low-humidity environments, ensuring stable image density and quality by facilitating charge release, thus overcoming the limitations of existing technologies.
Patent Information
- Application Number
- JP2021066690
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-09
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-04-09
AI Technical Summary
Magnetic carriers used in two-component developers face challenges in maintaining stable image density after prolonged use in low-humidity environments due to excessive charging, leading to electrostatic attraction between the carrier and toner, which affects image quality.
The magnetic carrier is designed with a core made of porous magnetic particles filled with a resin containing a first resin and a second resin, where the first resin is polyrotaxane, which allows for high molecular mobility, facilitating the release of excess charge and preventing excessive charging.
The magnetic carrier maintains desired image density even after continuous output in low-humidity environments by effectively managing charge accumulation, reducing electrostatic attraction, and ensuring consistent image quality over time.
Smart Images

Figure 0007612492000001 
Figure 0007612492000002 
Figure 0007612492000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a magnetic carrier, a method for producing the magnetic carrier, a two-component developer, and a replenishment developer. [Background technology]
[0002] In the developer of an electrophotographic image forming apparatus, a two-component developer is widely used, which is obtained by mixing a magnetic carrier and a toner, frictionally charging the toner, imparting an appropriate amount of positive or negative charge to the toner, and developing the toner with the charge as a driving force. In recent years, there has been a demand for longer life for image forming apparatuses, and therefore the magnetic carrier used in the two-component developer is required to exhibit stable characteristics over a long period of time.
[0003] As a magnetic carrier that shows stable characteristics over a long period of time, a magnetic carrier in which the surface of a low specific gravity carrier core, which is made of porous magnetic particles filled with resin, is coated with resin, is known. Patent Document 1 discloses a magnetic carrier in which the surface of a magnetic carrier core, which is made of porous ferrite particles containing oxides of Sr and Ca, filled with resin in their pores, is coated with a vinyl resin. It is disclosed that this makes it possible to provide a magnetic carrier that can stably impart charge to a toner over a long period of time, has good toner release properties, and is excellent in developability. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-6513 A [Patent Document 2] WO01 / 083566 [Patent Document 3] JP 2017-31258 A Summary of the Invention [Problem to be solved by the invention]
[0005] One aspect of the present disclosure is to provide a magnetic carrier that can obtain an image with a desired density even after continuous image output for a long period of time in a low-humidity environment.
[0006] Another aspect of the present disclosure is directed to providing a method for producing the magnetic carrier according to the present disclosure.
[0007] Another aspect of the present disclosure is directed to providing a two-component developer having the magnetic carrier according to the present disclosure.
[0008] Another aspect of the present disclosure is directed to providing a refill developer having a magnetic carrier according to the present disclosure. [Means for solving the problem]
[0009] According to one aspect of the present disclosure, there is provided a magnetic carrier having a magnetic carrier core particle and a surface layer covering the surface of the magnetic carrier core particle, The magnetic carrier core particles have a resin present in at least a part of the voids of the porous magnetic particles, The resin includes a first resin and a second resin different from the first resin, the first resin is a polyrotaxane; The polyrotaxane is (i) a plurality of cyclic molecules; (ii) a chain molecule that is pierced and included in the ring of the cyclic molecule; having (iii) the chain molecule has two or more blocking groups that prevent the cyclic molecule from being detached from the chain molecule; The magnetic carrier is characterized by the above.
[0010] According to another aspect of the present disclosure, there is provided a method for producing a magnetic carrier according to the present disclosure, comprising the steps of: The manufacturing method includes a step of filling the voids of the porous magnetic particles with a mixture of the first resin and a raw material of the second resin. A method for producing a magnetic carrier is provided.
[0011] According to another aspect of the present disclosure, there is provided a two-component developer containing a toner and a magnetic carrier, The magnetic carrier is the magnetic carrier according to the present disclosure. The present invention provides a two-component developer comprising:
[0012] According to another aspect of the present disclosure, there is provided a replenishment developer containing a toner and a magnetic carrier, comprising: The magnetic carrier is the magnetic carrier according to the present disclosure. The present invention provides a replenishment developer comprising: Effect of the Invention
[0013] According to one aspect of the present disclosure, it is possible to provide a magnetic carrier that can obtain an image with a desired density even after continuous image output for a long period of time in a low humidity environment.
[0014] According to another aspect of the present disclosure, a method for producing the magnetic carrier according to the present disclosure can be provided.
[0015] According to another aspect of the present disclosure, a two-component developer having the magnetic carrier according to the present disclosure can be provided.
[0016] According to another aspect of the present disclosure, a refill developer having the magnetic carrier according to the present disclosure can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] In the present disclosure, the expressions "xx or more and xx or less" and "xx to xx" expressing a numerical range mean a numerical range including the endpoints, that is, the lower limit and the upper limit, unless otherwise specified.
[0018] In the present disclosure, (meth)acrylic acid means acrylic acid and / or methacrylic acid.
[0019] <Background to the invention> As with the magnetic carrier described in Patent Document 1, a magnetic carrier in which the surface of a low specific gravity carrier core, which is made of porous magnetic particles filled with resin, is covered with a surface layer can exhibit stable characteristics over a long period of time.
[0020] Meanwhile, while studying the above magnetic carrier, the present inventors discovered that after continuous image output for a long period of time in a low humidity environment, it may become difficult to obtain an image of the desired density.
[0021] The present inventors speculate that one of the causes of this phenomenon is that when the above-mentioned image output is performed, electric charges continue to accumulate in the resin filled in the magnetic carrier, which makes the magnetic carrier more likely to be excessively charged. As a result, it is considered that the excessive electric charges accumulated in the magnetic carrier generate electrostatic attraction, which makes it easier for the toner to be pulled back to the carrier side, making it difficult to obtain a desired image density. From the viewpoint of obtaining high-quality images over a long period of time, it is naturally required that the image can be output at the image density desired by the user. Therefore, the present inventors have recognized that it is necessary to develop a technology that can release the excessive electric charges that continue to accumulate in the magnetic carrier and output the desired image density even after continuing to output images for a long period of time in a low-humidity environment.
[0022] Based on the above considerations, the present inventors have investigated various materials to obtain a magnetic carrier capable of outputting an image at a desired density even after long periods of image output in a low humidity environment. As a result of intensive investigations, they have found that filling porous magnetic particles with a resin material containing polyrotaxane is effective in realizing a magnetic carrier having the above-mentioned characteristics.
[0023] Since the cyclic molecules contained in the polyrotaxane can rotate and move along the chain molecules, the polyrotaxane is a material with high molecular mobility. The inventors believe that by including such a material with high molecular mobility, the charge generated in the resin present in the voids of the porous magnetic particles can be easily moved, and this makes it easier to release excess charge accumulated in the resin. As a result, the inventors speculate that the magnetic carrier is unlikely to be excessively charged even in a low humidity environment, and the electrostatic attraction between the carrier and the toner is unlikely to become excessive, making it easier to obtain the desired image density.
[0024] <Polyrotaxane> The resin according to the present disclosure contains a first resin, which is a polyrotaxane. The polyrotaxane has (i) a plurality of cyclic molecules, (ii) a linear molecule that is skewered and included in the rings of the cyclic molecules, and (iii) the linear molecule has two or more blocking groups that prevent the cyclic molecules from being detached from the linear molecule.
[0025] Generally, a molecular assembly in which a chain molecule penetrates the inside of the ring of a cyclic molecule and a bulky molecule is bonded to the end of the axis, binding the cyclic molecule to the chain molecule, is called a rotaxane. A molecular assembly in which many cyclic molecules are linked to one chain molecule is called a polyrotaxane. The cyclic molecule is not bonded to the chain molecule, and can rotate and move on the chain molecule.
[0026] In order to easily obtain the effects of the present disclosure, the content of the first resin in the resin according to the present disclosure is preferably 1.0% by mass or more and 30.0% by mass or less, and more preferably 5.0% by mass or more and 25.0% by mass or less.
[0027] The polyrotaxane of the present disclosure can be produced by a known method, for example, the method described in Patent Document 2 or Patent Document 3, or can be obtained and used as a commercially available product (product name: CELME Super Polymer, manufactured by ASM Co., Ltd.). The polyrotaxane is preferably dispersed and contained in the resin according to the present disclosure.
[0028] In addition, the polyrotaxane according to the present disclosure may be a polyrotaxane bound to a polymer, but the polymer bound to the polyrotaxane is treated as a part of the polyrotaxane according to the present disclosure and is not treated as the second resin according to the present disclosure. In other words, the second resin according to the present disclosure is treated as a resin according to the present disclosure that is not bound to the polyrotaxane.
[0029] In the polyrotaxane of the present disclosure, the number of cyclic molecules threaded into one linear molecule (the inclusion amount) is not particularly limited. The inclusion amount can be controlled by the molar ratio of the linear molecule and the cyclic molecule used in producing the polyrotaxane.
[0030] The configuration of the polyrotaxane according to the present disclosure will be described below.
[0031] <Cyclic molecules> The cyclic molecules contained in the polyrotaxane are not particularly limited as long as they are capable of including chain molecules and have a ring structure through which the chain molecules can penetrate in a skewered manner.
[0032] Examples of the cyclic molecule of the present disclosure include cyclodextrins, crown ethers, benzocrowns, dibenzocrowns, dicyclohexanocrowns, and derivatives or modified forms thereof. Among these, cyclodextrins are preferred because they are easy to include chain molecules. That is, the cyclic molecule is preferably a molecule having a cyclodextrin skeleton. More preferably, the cyclic molecule is a molecule having at least one cyclodextrin skeleton selected from the group consisting of an α-cyclodextrin skeleton, a β-cyclodextrin skeleton, and a γ-cyclodextrin skeleton.
[0033] The cyclic molecule may be of one type, or of two or more types in combination.
[0034] In the present disclosure, a molecule having a cyclodextrin skeleton is regarded as a cyclodextrin molecule, or a molecule having a structure synthesized when a derivatization reaction is carried out on a hydroxyl group of a cyclodextrin molecule.
[0035] <Side chains attached to cyclodextrin> It is preferable that the cyclic molecule of the polyrotaxane is a molecule having a cyclodextrin skeleton, and the molecule having the cyclodextrin skeleton has cyclodextrin and a side chain bonded to the cyclodextrin. Here, the side chain bonded to the cyclodextrin in the present disclosure is treated as a partial structure introduced when a derivatization reaction is performed on a hydroxy group of the cyclodextrin. The side chain may be a linear structure or a branched structure.
[0036] It is considered that the affinity between the polyrotaxane and the second resin is easily increased by the above-mentioned side chain. As a result, it is considered that the presence state of the polyrotaxane is less likely to be biased and is easily contained in a uniformly dispersed state, and the effect of the present disclosure is easily obtained. In addition, it is more preferable that the side chain has a polymer structure. In addition, it is preferable that the side chain has a polyester structure, a vinyl polymer structure, a polyurethane structure, a polyurea structure, or a polyether structure. It is more preferable that the side chain has a vinyl polymer structure or a polyester structure. Examples of the polyester structure include a polymer structure in which a diol and a dicarboxylic acid are condensed, and a polycaprolactone structure. In addition, the vinyl polymer structure is a polymer structure in which a vinyl monomer is polymerized, and examples thereof include a styrene-methyl methacrylate polymer structure and a styrene-methyl acrylate polymer structure.
[0037] The weight-average molecular weight of the molecule having a cyclodextrin skeleton and the above-mentioned side chain is preferably 2500 to 50000. More preferably, it is 2500 to 10000. It is believed that within the above range makes it easier for the polyrotaxane and the second resin to be entangled, makes it easier for the polyrotaxane to be contained in a dispersed state, and also makes it easier for electric charges to escape, which has been found to make it easier to obtain a desired image density.
[0038] A molecule having a cyclodextrin skeleton satisfying the above weight average molecular weight can be produced, for example, by introducing a polyester structure into the hydroxyl group of cyclodextrin, or by a vinyl polymerization reaction between a cyclodextrin derivative having a vinyl polymerizable double bond and a vinyl monomer.
[0039] The molecular weight of the cyclic molecule can be measured by an analytical device such as GPC after isolating the cyclic molecule. In order to isolate the cyclic molecule, the terminal blocking groups of the polyrotaxane must be removed as a first step. For example, in the case of polyrotaxanes having terminal blocking groups bonded with amide groups or carbonyl groups, a method of heating under acid or base conditions and hydrolyzing the polyrotaxane can be used. The cyclic molecule can then be isolated by a conventional method such as reprecipitation, filtration, centrifugation, or membrane separation.
[0040] <chain molecule> The chain molecule of the polyrotaxane is not particularly limited as long as it can pierce the cyclic molecule in a skewered manner, is included in the cyclic molecule, and allows the cyclic molecule to rotate, slide, or move freely. The length of the chain molecule is also not particularly limited. The chain molecule is preferably a linear molecule. In the present disclosure, a linear molecule is considered to be a molecule having no branch in the main chain of the molecule.
[0041] The chain molecule is preferably at least one selected from the group consisting of polyalkylenes, polyesters, polyethers, polyamides, and polyacrylics, and among these, polyethers are more preferable. That is, the chain molecule is preferably a molecule having a polyether chain. More preferably, it is a molecule having a polyalkylene glycol chain, and even more preferably, it is a molecule having a polyethylene glycol chain.
[0042] <Blocking group> The chain molecule has two or more blocking groups at its terminals to prevent the cyclic molecules from being released. The blocking groups of the polyrotaxane can be used without any particular limitation as long as they can prevent the cyclic molecules from being released. Examples of the blocking groups according to the present disclosure include bulky groups for physically preventing the cyclic molecules from being released, and ionic groups for electrically preventing the cyclic molecules from being released. Specific examples include dinitrophenyl groups, adamantyl groups, trityl groups, and pyrenyl groups. Specific examples include cyclodextrins and fluoresceins that are introduced as substituents at the terminals of the chain molecules. The blocking groups may also be derivatives or modified forms of the above.
[0043] <Bonded polyrotaxane> The cyclic molecules of the two or more polyrotaxanes may be bonded to each other by forming a chemical bond between them.
[0044] That is, the polyrotaxane according to the present disclosure includes a bound polyrotaxane formed by binding a first polyrotaxane and a second polyrotaxane, The first polyrotaxane and the second polyrotaxane may be bonded by a chemical bond between a cyclic molecule contained in the first polyrotaxane and a cyclic molecule contained in the second polyrotaxane.
[0045] The above-mentioned bound polyrotaxane can be obtained, for example, by reacting a polyrotaxane having cyclodextrin with a compound having epoxy groups at both ends (for example, 1,4-butanediol diglycidyl ether, etc.) in a basic aqueous solution.
[0046] Furthermore, a plurality of cyclic molecules contained in one polyrotaxane may be bonded to each other by forming a chemical bond.
[0047] In the present disclosure, a chemical bond may be a single bond or a bond via various atoms or molecules (eg, a bond via a linking group).
[0048] <Magnetic carrier> The magnetic carrier of the present disclosure is a magnetic carrier having a magnetic carrier core particle and a surface layer covering the surface thereof, and the magnetic carrier core particle has a resin present in at least a part of the voids of the porous magnetic particle. The content ratio of the resin according to the present disclosure to the porous magnetic particle is preferably 2.0% by mass or more and 15.0% by mass or less. More preferably, it is 2.5% by mass or more and 12.0% by mass or less.
[0049] <Magnetic carrier core particles> The magnetic carrier core particles have a resin present at least in part in the voids of the porous magnetic particles. By using such core particles, the true density of the magnetic carrier can be reduced, so that the load on the toner can be reduced, image quality is less likely to deteriorate even with long-term use, and the frequency of replacing the developer composed of the toner and carrier can be reduced.
[0050] <Porous magnetic particles> As the material for the porous magnetic particles, magnetite or ferrite is preferred, and ferrite is more preferred, because it is easy to control the porous structure and adjust the resistance.
[0051] Ferrite is a sintered body represented by the following general formula: (M12O) x(M2O) y (Fe2O3) z (In the formula, M1 is a monovalent metal, M2 is a divalent metal, and when x+y+z=1.0, x and y are each 0≦(x,y)≦0.8, and z is 0.2 <z<1.0である。) In the formula, it is preferable to use at least one metal atom selected from the group consisting of Li, Fe, Mn, Mg, Sr, Cu, Zn, and Ca as M1 and M2, as well as Ni, Co, Ba, Y, V, Bi, In, Ta, Zr, B, Mo, Na, Sn, Ti, Cr, Al, Si, and rare earth elements.
[0052] In the magnetic carrier, it is preferable to control the surface roughness of the porous magnetic particles in order to maintain the magnetization amount at a suitable level and to set the pore size within a desired range. It is also preferable to be able to easily control the speed of the ferritization reaction and to suitably control the resistivity and magnetic force of the porous magnetic core. From the above viewpoints, Mn-based ferrites, Mn-Mg-based ferrites, Mn-Mg-Sr-based ferrites, and Li-Mn-based ferrites containing Mn element are more preferable.
[0053] <Second resin> The magnetic carrier core particles according to the present disclosure have a resin present in at least a part of the voids of the porous magnetic particles, and the resin includes a first resin and a second resin different from the first resin. The second resin may be either a thermoplastic resin or a thermosetting resin, but is preferably one that has a high affinity for the porous magnetic particles. When a resin with a high affinity is used, the resin can be filled into the voids of the porous magnetic particles and the surface of the porous magnetic particles can be covered with the resin at the same time.
[0054] The thermoplastic resin preferred as the second resin is at least one selected from the group consisting of novolac resins, saturated alkyl polyester resins, polyarylates, polyamide resins, and acrylic resins.
[0055] The thermosetting resin preferably used as the second resin is at least one selected from the group consisting of phenolic resins, epoxy resins, unsaturated polyester resins, and silicone resins. Among these, silicone resins are more preferable from the viewpoint of filling the porous magnetic particles.
[0056] The content of the second resin in the resin according to the present disclosure is preferably 60.0 to 99.0% by mass, and more preferably 70.0 to 95.0% by mass. <Surface layer> The surface layer according to the present disclosure is preferably a resin layer. The resin contained in the resin layer is preferably a vinyl resin. More preferably, it is a vinyl resin having a vinyl monomer unit having an alicyclic hydrocarbon group in the molecular structure. Also, a vinyl resin which is a copolymer of the vinyl monomer unit and another vinyl monomer is more preferable. More preferably, it is a copolymer of a monomer including a (meth)acrylic acid ester having an alicyclic hydrocarbon group and a macromonomer. Also, it is further preferably a copolymer of a (meth)acrylic acid ester having an alicyclic hydrocarbon group, a macromonomer, and another monomer.
[0057] In order to prevent image density from changing, the ratio of the mass of the resin contained in the resin layer to the mass of the magnetic carrier core particles is preferably 0.5% by mass or more and 6.0% by mass or less, more preferably 1.0% by mass or more and 5.0% by mass or less, and even more preferably 3.0% by mass or less.
[0058] <Magnetic carrier manufacturing example> A manufacturing process in which porous ferrite particles are used as the porous magnetic particles will be described in detail below.
[0059] <Process 1 (weighing and mixing process)> First, the raw materials for ferrite are weighed and mixed. Examples of the raw materials for ferrite include metal particles of the above-mentioned metal elements, or oxides, hydroxides, oxalates, carbonates, and the like. Examples of the mixing device include the following: ball mill, planetary mill, Giotto mill, and vibration mill. In particular, the ball mill is preferable from the viewpoint of mixability. Specifically, the weighed raw materials for ferrite and balls are placed in the ball mill, and the mixture is pulverized and mixed preferably for 0.1 to 20.0 hours.
[0060] <Step 2 (Pre-firing step)> The ground and mixed ferrite raw material is calcined in air or nitrogen atmosphere, preferably at a calcination temperature of 700° C. to 1200° C., for 0.5 to 5.0 hours, to form ferrite. For calcination, the following furnaces are used, for example: burner-type incinerator, rotary-type calciner, electric furnace, etc.
[0061] <Step 3 (Crushing step)> The calcined ferrite produced in step 2 is pulverized by a pulverizer. The pulverizer is not particularly limited as long as the desired particle size is obtained. Examples include the following. Examples include a crusher, a hammer mill, a ball mill, a bead mill, a planetary mill, and a Giotto mill. In order to obtain the desired particle size of the pulverized ferrite product, it is preferable to control the material, particle size, and operation time of the balls and beads used in the ball mill or bead mill. Specifically, in order to reduce the particle size of the calcined ferrite slurry, balls with a heavy specific gravity may be used or the pulverization time may be extended. In addition, in order to widen the particle size distribution of the calcined ferrite, balls or beads with a heavy specific gravity may be used and the pulverization time may be shortened. In addition, calcined ferrite with a wide distribution can be obtained by mixing multiple calcined ferrites with different particle sizes. In addition, in the case of ball mills and bead mills, wet methods are more preferable than dry methods because the pulverized product does not fly up in the mill and the pulverization efficiency is higher. For this reason, wet methods are more preferable than dry methods.
[0062] <Process 4 (granulation process)> Water, a binder, and, if necessary, a pore regulator are added to the pulverized calcined ferrite. Examples of the pore regulator include a foaming agent and resin particles. Examples of the foaming agent include sodium hydrogen carbonate, potassium hydrogen carbonate, lithium hydrogen carbonate, ammonium hydrogen carbonate, sodium carbonate, potassium carbonate, lithium carbonate, and ammonium carbonate.
[0063] As the binder, for example, polyvinyl alcohol is used.
[0064] Examples of resin fine particles include polyester, polystyrene, styrene copolymers such as styrene-vinyl toluene copolymers, styrene-vinyl naphthalene copolymers, styrene-acrylic acid ester copolymers, styrene-methacrylic acid ester copolymers, styrene-α-methyl chloromethacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, and styrene-acrylonitrile-indene copolymers; polyvinyl chloride, phenolic resins, modified phenolic resins, maleic resins, acrylic resins, methacrylic resins, polyvinyl acetate, and silicone resins; polyester resins having a monomer selected from aliphatic polyhydric alcohols, aliphatic dicarboxylic acids, aromatic dicarboxylic acids, aromatic dialcohols, and diphenols as a structural unit; polyurethane resins, polyamide resins, polyvinyl butyral, terpene resins, coumarone-indene resins, petroleum resins, and hybrid resins having a polyester unit and a vinyl polymer unit.
[0065] In step 3, when wet pulverization is performed, it is preferable to take into consideration the water contained in the ferrite slurry and to add a binder and, if necessary, a pore regulator.
[0066] The obtained ferrite slurry is dried and granulated using a spray dryer, preferably in a heated atmosphere of 100° C. to 200° C. The spray dryer is not particularly limited as long as it can obtain the desired particle size of the porous magnetic particles. For example, a spray dryer can be used.
[0067] <Step 5 (Main Firing Step)> Next, the granulated product is sintered, preferably at a temperature of 800° C. to 1400° C. for 1 hour to 24 hours. By increasing the sintering temperature and the sintering time, the sintering of the porous magnetic particles proceeds, resulting in a smaller pore size and a reduced number of pores.
[0068] <Step 6 (Sorting step)> After the sintered particles are crushed as described above, they may be classified or sieved to remove coarse particles and fine particles, if necessary. From the viewpoint of image density and gradation reproducibility, the volume distribution 50% particle size (D50) of the porous magnetic particles is preferably 18.0 μm or more and 68.0 μm or less.
[0069] <Process 7 (filling process)> The resin used here is preferably a mixture of the raw materials of the first resin and the second resin. That is, the manufacturing method of the magnetic carrier according to the present disclosure preferably has a step of filling the voids of the porous magnetic particles with a mixture of the first resin and the raw materials of the second resin. Other additives may be contained as necessary. This can be added to the voids of the porous magnetic core and filled by a method of removing the solvent.
[0070] The method of filling the voids of the porous magnetic particles with a resin is not particularly limited, but includes a method of impregnating the porous magnetic particles with a resin solution by a coating method such as a dipping method, a spraying method, a brush coating method, or a fluidized bed, and then volatilizing the solvent. Also usable is a method of diluting the resin in a solvent and adding this to the voids of the porous magnetic particles.
[0071] The solvent used here may be any solvent capable of dissolving the resin. In the case of a resin soluble in an organic solvent, examples of the organic solvent include toluene, xylene, cellosolve butyl acetate, methyl ethyl ketone, methyl isobutyl ketone, and methanol. In the case of a water-soluble resin or an emulsion-type resin, water may be used as the solvent.
[0072] The amount of resin solids in the resin solution is preferably 1% by mass or more and 50% by mass or less, more preferably 1% by mass or more and 30% by mass or less. If it is 50% by mass or less, the viscosity is not too high and the resin solution is likely to uniformly penetrate into the voids of the porous magnetic particles. On the other hand, if it is 1% by mass or more, the amount of resin is appropriate and the adhesion of the resin to the porous magnetic particles is good. Thereafter, the method of coating the surface of the magnetic carrier core particles with resin is not particularly limited, but includes coating methods such as dipping, spraying, brushing, dry method, and fluidized bed coating.
[0073] In addition, conductive particles or particles or materials having charge control properties may be contained in the resin layer that covers the surface of the magnetic carrier core particles. Examples of conductive particles include carbon black, magnetite, graphite, zinc oxide, and tin oxide. The amount of conductive particles added is preferably 0.1 parts by mass or more and 10.0 parts by mass or less per 100 parts by mass of the resin in the resin layer in order to adjust the resistance of the magnetic carrier. Examples of particles having charge control properties include the following.
[0074] Particles of organic metal complexes, particles of organic metal salts, particles of chelate compounds, particles of monoazo metal complexes, particles of acetylacetone metal complexes, particles of hydroxycarboxylic acid metal complexes, particles of polycarboxylic acid metal complexes, particles of polyol metal complexes, etc. Also, particles of polymethyl methacrylate resins, particles of polystyrene resins, particles of melamine resins, particles of phenolic resins, particles of nylon resins, particles of silica, particles of titanium oxide, particles of alumina, etc.
[0075] The amount of the particles having charge control properties added is preferably 0.5 parts by mass or more and 50.0 parts by mass or less with respect to 100 parts by mass of the resin in the resin layer in order to adjust the amount of triboelectric charge.
[0076] <Two-component developer> The two-component developer according to the present disclosure is a two-component developer containing a toner and a magnetic carrier, and is characterized in that the magnetic carrier is the magnetic carrier according to the present disclosure.
[0077] When the toner is mixed with the magnetic carrier, good results are usually obtained when the carrier mixing ratio is, in terms of the toner concentration in the developer, preferably 2% by mass or more and 15% by mass or less, and more preferably 4% by mass or more and 13% by mass or less.
[0078] When used as a replenishing developer, the toner is preferably contained in an amount of 2 parts by mass or more and 50 parts by mass or less per part by mass of the magnetic carrier.
[0079] <Toner> Next, a preferred toner configuration will be described in detail.
[0080] The toner has toner particles containing a binder resin and, if necessary, a colorant and a release agent. Examples of the binder resin include vinyl resin, polyester resin, and epoxy resin. Among them, vinyl resin and polyester resin are more preferable in terms of chargeability and fixability. Polyester resin is particularly preferable. In addition, the following materials can be mixed with the binder resin if necessary.
[0081] Homopolymers or copolymers of vinyl monomers, polyesters, polyurethanes, epoxy resins, polyvinyl butyral, rosin, modified rosin, terpene resins, phenolic resins, aliphatic or alicyclic hydrocarbon resins, aromatic petroleum resins, and the like.
[0082] When two or more kinds of resins are mixed and used as the binder resin, it is more preferable to mix resins having different molecular weights in an appropriate ratio.
[0083] The glass transition temperature of the binder resin is preferably 45° C. or more and 80° C. or less, more preferably 55° C. or more and 70° C. or less. The number average molecular weight (Mn) is preferably 2500 or more and 50,000 or less. The weight average molecular weight (Mw) is preferably 10,000 or more and 1,000,000 or less.
[0084] As the binder resin, the following polyester resin is also preferred.
[0085] Based on all monomer units constituting the polyester resin, it is preferable that the alcohol component accounts for 45 mol % or more and 55 mol % or less, and the acid component accounts for 45 mol % or more and 55 mol % or less.
[0086] The glass transition temperature of the polyester resin is preferably 50° C. or more and 75° C. or less, more preferably 55° C. or more and 65° C. or less. The number average molecular weight (Mn) is preferably 1500 or more and 50,000 or less, more preferably 2000 or more and 20,000 or less. The weight average molecular weight (Mw) is preferably 6000 or more and 100,000 or less, more preferably 10,000 or more and 90,000 or less.
[0087] <Various additives> If necessary, the toner may contain one or more additives selected from a colorant, a wax, a charge control agent, inorganic fine particles, etc. Various additives used in the toner will be specifically described.
[0088] <Coloring agent> The colorant is preferably non-magnetic. Examples of the colorant include the following:
[0089] Examples of black colorants include carbon black, and black colorants prepared by using a yellow colorant, a magenta colorant, and a cyan colorant.
[0090] Examples of color pigments for magenta toner include condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds.Specific examples include CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81: 1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 144, 146, 150, 163, 166, 169, 177, 184, 185, 202, 206, 207, 209, 220, 221, 238, 254, 269; CI Pigment Violet 19, CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35.
[0091] As the colorant, a pigment may be used alone, but it is preferable to use a dye and a pigment in combination to improve the clarity of the image from the viewpoint of the image quality of a full color image.
[0092] Dyes for magenta toner include the following: solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121, CI Disperse Red 9, CI Solvent Violet 8, 13, 14, 21, 27, CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40, CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.
[0093] Examples of color pigments for cyan toners include: CI Pigment Blue 1, 2, 3, 7, 15:2, 15:3, 15:4, 16, 17, 60, 62, 66; CI Bat Blue 6, CI Acid Blue 45, and copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton.
[0094] Examples of yellow coloring pigments include the following: condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal compounds, methine compounds, and allylamide compounds.
[0095] Specifically, CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 155, 168, 174, 180, 181, 185, 191; CI Bat Yellow 1, 3, 20. In addition, dyes such as CI Direct Green 6, CI Basic Green 4, CI Basic Green 6, and Solvent Yellow 162 can also be used.
[0096] The amount of the colorant used is preferably 0.1 parts by mass or more and 30 parts by mass or less, more preferably 0.5 parts by mass or more and 20 parts by mass or less, and even more preferably 3 parts by mass or more and 15 parts by mass or less, based on 100 parts by mass of the binder resin.
[0097] The method for producing the toner is not particularly limited, and any known method can be used, such as a melt kneading method, a suspension polymerization method, a dissolution suspension method, or an emulsion aggregation method.
[0098] In the toner, it is preferable to use a master batch in which a colorant is mixed in advance with a binder resin, and the colorant master batch is melt-kneaded with other raw materials (binder resin, wax, etc.) to disperse the colorant well in the toner.
[0099] <Charge control agent> In order to further stabilize the chargeability of the toner, a charge control agent can be used as necessary. The charge control agent is preferably used in an amount of 0.5 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the binder resin. If the amount is 0.5 parts by mass or more, sufficient charging characteristics can be obtained. On the other hand, if the amount is 10 parts by mass or less, compatibility with other materials is good, and excessive charging under low humidity conditions can be suppressed.
[0100] The charge control agent includes the following.
[0101] As a negative charge control agent for controlling the toner to be negatively charged, for example, an organic metal complex or a chelate compound is effective. Examples of the negative charge control agent include monoazo metal complexes, metal complexes of aromatic hydroxycarboxylic acids, and metal complexes of aromatic dicarboxylic acids. Other examples include aromatic hydroxycarboxylic acids, aromatic mono- and polycarboxylic acids and their metal salts, their anhydrides, or their esters, or phenol derivatives of bisphenol.
[0102] Examples of positive charge control agents that control the toner to be positively charged include modified products of nigrosine and fatty acid metal salts, quaternary ammonium salts such as tributylbenzylammonium-1-hydroxy-4-naphthosulfonate and tetrabutylammonium tetrafluoroborate, and onium salts such as phosphonium salts that are analogues of these, and chelate pigments thereof such as triphenylmethane dyes and lake pigments thereof (lake forming agents include phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanide compounds, etc.), and metal salts of higher fatty acids such as diorganotin oxides such as dibutyltin oxide, dioctyltin oxide, and dicyclohexyltin oxide, and diorganotin borates such as dibutyltin borate, dioctyltin borate, and dicyclohexyltin borate.
[0103] <Release agent> Examples of the release agent include the following:
[0104] Low molecular weight polyethylene, low molecular weight polypropylene, microcrystalline wax, paraffin wax, and other aliphatic hydrocarbon waxes are preferably used.
[0105] Oxidized aliphatic hydrocarbon waxes such as oxidized polyethylene wax, or their block copolymers. Waxes whose main component is fatty acid esters such as carnauba wax and montan acid ester wax. Partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax.
[0106] The amount of the release agent is preferably 0.1 parts by mass or more and 20 parts by mass or less, and more preferably 0.5 parts by mass or more and 10 parts by mass or less, per 100 parts by mass of the binder resin.
[0107] The melting point of the release agent, which is determined by the maximum endothermic peak temperature during heating measured by a differential scanning calorimeter (DSC), is preferably 65° C. or higher and 130° C. or lower, and more preferably 80° C. or higher and 125° C. or lower.
[0108] <External additives> Examples of the external additive include the following.
[0109] Fluorine-based resin powders such as vinylidene fluoride fine powder and polytetrafluoroethylene fine powder; fine silica powders such as wet-processed silica and dry-processed silica, fine titanium oxide powder, fine alumina powder, etc. Furthermore, these are surface-treated with a silane coupling agent, a titanium coupling agent, or silicone oil to be hydrophobized, and those treated so that the hydrophobicity measured by a methanol titration test is in the range of 30 to 80 are particularly preferred.
[0110] The amount of the external additive used is preferably 0.1 parts by mass or more and 10 parts by mass or less, and more preferably 0.2 parts by mass or more and 8 parts by mass or less, based on 100 parts by mass of the toner particles.
[0111] <Various measurement methods> <Method for measuring volume average particle size (D50)> Particle size distribution measurements are performed using a laser diffraction / scattering particle size distribution measuring device, Microtrac MT3300EX (manufactured by Nikkiso Co., Ltd.). In addition, a sample supply device for dry measurements, One-Shot Dry Sample Conditioner Turbotrac (manufactured by Nikkiso Co., Ltd.), is attached. The supply conditions for Turbotrac are a dust collector as the vacuum source, with an air volume of approximately 33 l / sec and a pressure of approximately 17 kPa. Control is performed automatically on the software. Particle size is calculated as the 50% particle size (D50), which is the cumulative value of the volume average. Control and analysis are performed using the accompanying software (version 10.3.3-202D). The measurement conditions are as follows: SetZero time: 10 seconds Measurement time: 10 seconds Number of measurements: 1 Particle refractive index: 1.81% ·Particle shape: non-spherical Upper limit of measurement: 1408μm ·Measurement lower limit: 0.243μm Measurement environment: 23℃, 50% RH
[0112] <Measurement of pore size and pore volume of porous magnetic particles> The pore size distribution of the porous magnetic particles is measured by mercury intrusion porosimetry. Measurement equipment includes fully automatic multi-function mercury porosimeters PoreMaster series and PoreMaster-GT series manufactured by Yuasa Ionics, and automatic porosimeters AutoPore IV 9500 series manufactured by Shimadzu Corporation. In this disclosure, measurements are performed using Shimadzu AutoPore IV 9520 under the following conditions and procedures.
[0113] Measurement conditions Measurement environment: 20℃ Measurement cell sample volume 5cm 3 , Pressurized volume 1.1cm 3 , Application for powder Measurement range: 2.0psia (13.8kPa) or more, 59989.6psia (413.7kPa) or less · Measurement step 80 steps (steps are marked at equal intervals when taking the logarithm of the pore diameter) · Penetration parameters Exhaust pressure 50 μmHg, exhaust time 5.0 min, mercury injection pressure 2.0 psia (13.8 kPa), at equilibrium 5 secs · High-pressure parameters Equilibrium time 5 secs · Mercury parameters Advancing contact angle 130.0 degrees, receding contact angle 130.0 degrees, surface tension 485.0 mN / m (485.0 dynes / cm), mercury density 13.5335 g / mL Measurement procedure (1) Weigh approximately 1.0 g of the porous magnetic particles, put them into the sample cell, and input the weighed value. (2) Measure in the low-pressure section in the range of 2.0 psia (13.8 kPa) or more and 45.8 psia (315.6 kPa) or less. (3) Measure in the high-pressure section in the range of 45.9 psia (316.3 kPa) or more and 59989.6 psia (413.6 kPa) or less. (4) Calculate the pore size distribution from the mercury injection pressure and the mercury injection volume. (2), (3), and (4) are automatically performed by the software attached to the device.
[0114] From the pore size distribution measured as described above, read the pore size at which the differential pore volume in the pore size range of 0.1 μm or more and 3.0 μm or less is maximum, and use it as the pore size at which the differential pore volume is maximum. Also, calculate the pore volume by integrating the differential pore volume in the pore size range of 0.1 μm or more and 3.0 μm or less using the attached software, and use it as the pore volume.
[0115] <Measurement of weight-average molecular weight by GPC> The molecular weight distribution of the sample is measured by gel permeation chromatography (GPC) as follows.
[0116] First, a sample is dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The resulting solution is then filtered through a solvent-resistant membrane filter "Maeshori Disk" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of components soluble in THF is approximately 0.8 mass%. This sample solution is used to perform measurements under the following conditions. Equipment: HLC8120 GPC (detector: RI) (Tosoh Corporation) Column: 7 columns of Shodex KF-801, 802, 803, 804, 805, 806, 807 (Showa Denko Co., Ltd.) Eluent: Tetrahydrofuran (THF) ·Flow rate: 1.0ml / min Oven temperature: 40.0℃ Sample injection volume: 0.10ml In calculating the molecular weight of a sample, a molecular weight calibration curve prepared using standard polystyrene resins (e.g., trade names "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation) is used.
[0117] <Method of measuring weight average particle size (D4) of toner particles> The weight-average particle diameter (D4) of the toner particles was measured using a precision particle size distribution measuring device using the pore electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), for setting measurement conditions and analyzing measurement data. Measurements were made with an effective measurement channel count of 25,000 channels, and the measurement data was analyzed and calculated.
[0118] The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter).
[0119] Before performing the measurements and analysis, the dedicated software was set up as follows.
[0120] In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement.
[0121] In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range from 2 μm to 60 μm.
[0122] The specific measurement method is as follows. (1) Pour about 200 ml of the electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, remove dirt and air bubbles from inside the aperture tube using the "Aperture Tube Flush" function of the dedicated software. (2) About 30 ml of the electrolyte solution is placed in a 100 ml flat-bottom glass beaker, and about 0.3 ml of a dilution of "Contaminon N" (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments, made from a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted three times by mass with ion-exchanged water is added as a dispersant. (3) A specified amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees and an electrical output of 120 W. Approximately 2 ml of the Conaminon N is added to this water tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner particles are added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, the electrolyte solution (5) in which the toner particles are dispersed is dropped into the round-bottom beaker (1) placed in the sample stand, and the measurement concentration is adjusted to about 5%. Then, the measurement is continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle size (D4).
[0123] <Measurement of resin glass transition temperature (Tg)> The glass transition temperature of the resin is measured using a differential scanning calorimeter "Q2000" (manufactured by TA Instruments) in accordance with ASTM D3418-82.
[0124] The melting points of indium and zinc are used for temperature correction of the device detection section, and the heat of fusion of indium is used for heat correction. Specifically, about 5 mg of resin is precisely weighed and placed in an aluminum pan, and an empty aluminum pan is used as a reference. Measurements are performed at a temperature rise rate of 10°C / min in the measurement range of 30°C to 180°C.
[0125] The temperature is first raised to 180°C and held there for 10 minutes, then lowered to 30°C, and then raised again. During this second heating process, a specific heat change is obtained in the temperature range of 30°C to 100°C. The glass transition temperature (Tg:°C) of the resin is determined by the temperature at the point where a line equidistant in the vertical direction from a line extending the baseline before and after the specific heat change occurs intersects with the curve of the stepwise change in the glass transition in the DSC curve. EXAMPLES
[0126] Hereinafter, the present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited to these examples. In the following formulations, parts are by weight unless otherwise specified.
[0127] First, examples of the preparation of materials used in each example will be described.
[0128] <Toner 1 Manufacturing Example> Binder resin 100.0 parts (Tg: 57℃ polyester) CI Pigment Blue 15:3 5.5 parts 0.1 parts of 3,5-di-t-butylsalicylic acid aluminum compound Normal paraffin wax (melting point: 90°C) 6.0 parts The above-mentioned materials were thoroughly mixed in a Henschel mixer (FM-75J, manufactured by Nippon Coke & Engineering Co., Ltd.). Then, the mixture was mixed at a feed rate of 10 kg / hr in a twin-screw mixer (product name: PCM-30, manufactured by Ikegai Steel Co., Ltd.) set at a temperature of 130°C (the temperature of the mixture when discharged was 150°C). The mixture was cooled, coarsely crushed in a hammer mill, and then finely crushed at a feed rate of 15 kg / hr in a mechanical crusher (product name: T-250, manufactured by Turbo Kogyo Co., Ltd.). Then, particles having a weight-average particle size of 5.5 μm, containing 55.6% by number of particles with a particle size of 4.0 μm or less and 0.8% by volume of particles with a particle size of 10.0 μm or more were obtained.
[0129] The obtained particles were classified using a rotary classifier (product name: TTSP100, manufactured by Hosokawa Micron Corp.) to remove fine powder and coarse powder. Toner particles 1 were obtained having a weight average particle size of 6.0 μm, a particle content of 4.0 μm or less being 27.8% by number, and a particle content of 10.0 μm or more being 2.2% by volume.
[0130] Furthermore, the following materials were charged into a Henschel mixer (product name: FM-75J type, manufactured by Nippon Coke & Engineering Co., Ltd.), and mixed at a rotating blade peripheral speed of 35.0 (m / sec) for a mixing time of 3 minutes to obtain Toner 1. Toner particles 1: 100.0 parts Silica particles: 1.0 parts (Silica particles with a number-average primary particle size of 10 nm, surface-treated with hexamethyldisilazane) Strontium titanate particles: 0.5 parts (Strontium titanate particles with a number-average primary particle size of 40 nm that have been surface-treated with an octylsilane compound.)
[0131] <Production Example of Coating Resin 1> 1.0 part of cyclohexyl methacrylate and 1.0 part of methyl methacrylate were added to a four-neck flask equipped with a reflux condenser, a thermometer, a nitrogen suction tube, and a grinding stirrer. Then, 3.0 parts of toluene, 3.0 parts of methyl ethyl ketone, and 0.072 parts of azobisisovaleronitrile were added, and the mixture was kept at 80°C for 10 hours under a nitrogen stream to obtain coating resin 1.
[0132] <Production Example of Polyrotaxane A1> The following materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stirred. 10.0g of the following polyrotaxane 1 (Polyrotaxane 1: SeRM Super Polymer SM1305P-20 (product name), manufactured by ASM. The chain molecule has a polyethylene glycol structure and an adamantyl group at the end of the chain molecule, and contains, as a cyclic molecule, multiple α-cyclodextrins having a polycaprolactone structure in the side chain. In addition, since the end of the side chain has a methacryl skeleton, it has a vinyl polymerizable carbon-carbon double bond.) 40mL of 1.0N NaOH solution 1,4-Butanediol diglycidyl ether (Tokyo Chemical Industry Co., Ltd.) 1.2 mL The mixture was stirred at 23°C for 24 hours to obtain a polyrotaxane in which the cyclic molecules were bonded together. After isolation, 600.0g of xylene, 150.0g of styrene, 50.0g of methyl methacrylate, and 1.5g of initiator t-butyl peroxypivalate were added, and polymerization was carried out for 3 hours while rotating the stirrer at 90°C to obtain a reaction product. The reaction product obtained was washed and dried to obtain polyrotaxane A1 in which cyclodextrin molecules were chemically bonded together and side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure were bonded to the cyclodextrin. The composition and physical properties are shown in Table 1.
[0133] <Production Example of Polyrotaxane A2> Into a reaction vessel equipped with a stirrer, a condenser, and a thermometer, 600.0 g of xylene, 10.0 g of the above polyrotaxane 1, and 15.0 g of epoxy-modified silicone resin (ES1001N; Shin-Etsu Chemical Co., Ltd.) were added. The temperature was maintained at 60°C while rotating the stirrer to obtain a reaction product. The reaction product was washed and dried to obtain polyrotaxane A2, in which side chains having a polycaprolactone structure and a silicone polymer structure are bonded to cyclodextrin. The composition and physical properties are shown in Table 1.
[0134] <Production example of Polyrotaxane A3> In a reaction vessel equipped with a stirrer, a condenser, and a thermometer, 600.0 g of xylene, 10.0 g of the above polyrotaxane 1, 150.0 g of styrene, 50.0 g of methyl methacrylate, and 1.5 g of initiator t-butyl peroxypivalate were added. Then, polymerization was carried out for 3 hours while rotating the stirrer and maintaining the temperature at 90°C, to obtain a reaction product. The reaction product obtained was washed and dried to obtain polyrotaxane A3, in which side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure are bonded to cyclodextrin. The composition and physical properties are shown in Table 1.
[0135] <Production example of polyrotaxane A4> Polyrotaxane A4 was obtained in the same manner as in the production example of Polyrotaxane A3, except that in the production example of Polyrotaxane A3, the above Polyrotaxane 1 was changed to the following Polyrotaxane 2, and methyl methacrylate was changed to methyl acrylate. Polyrotaxane A4 is a polyrotaxane in which side chains having a polycaprolactone structure and a styrene-methyl acrylate polymer structure are bonded to cyclodextrin. The composition and physical properties are shown in Table 1. Polyrotaxane 2: Selm Super Polymer SA1305P-20 (product name), manufactured by ASM. The chain molecule has a polyethylene glycol structure, an adamantyl group at the end of the chain molecule, and multiple α-cyclodextrins with polycaprolactone structures at the side chains as cyclic molecules. In addition, since the end of the side chain has an acrylic skeleton, it has a vinyl polymerizable carbon-carbon double bond.
[0136] <Production examples of polyrotaxanes A5, A6, and A8> Polyrotaxanes A5, A6, and A8 were obtained in the same manner as in the production example of polyrotaxane A3, except that the amounts of styrene and methyl methacrylate added were adjusted so that the molecular weight of the cyclic molecule would be the value in Table 1. Polyrotaxanes A5, A6, and A8 are polyrotaxanes in which side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure are bonded to cyclodextrin. The composition and physical properties are shown in Table 1.
[0137] <Production example of polyrotaxane A7> Polyrotaxane A7 was prepared using the above-mentioned Polyrotaxane 1. The composition and physical properties are shown in Table 1.
[0138] <Production example of polyrotaxane A9> Polyrotaxane A9 was prepared using the following polyrotaxane 3. The composition and physical properties are shown in Table 1. Polyrotaxane 3: Selm Super Polymer SH1310P (product name); manufactured by ASM. The chain molecule has a polyethylene glycol structure, an adamantyl group at the end of the chain molecule, and multiple α-cyclodextrins with polycaprolactone structures in the side chains as cyclic molecules. Also, a hydroxyl group is present at the end of the side chain.
[0139] <Production example of polyrotaxane A10> In 100 mL of pure water, add 2,2,6,6-tetramethyl-1-piperidinedioxy radical (TEMPO) (6.4 × 10 -4 mol) was added, and the pH was adjusted to 10 to 11. The following materials were added to this solution and stirred at room temperature for 10 to 15 minutes to oxidize the ends of the polyethylene glycol. Sodium bromide 9.7×10 -4 Mol 10mL of 13% sodium hypochlorite solution Polyethylene glycol (Aldrich) n=35,000 7.0×10 -4 Mol Then, 10 ml of ethanol was added, the pH was adjusted to 2, and dichloromethane extraction was performed three times using 100 ml of dichloromethane.
[0140] The dichloromethane extract was evaporated to dryness under reduced pressure, dissolved in ethanol at 40-50°C, frozen for one day and night, and then polyethylene glycol with a carboxylic acid terminal group (hereinafter referred to as PEG-COOH) was collected by centrifugation. The obtained PEG-COOH was freeze-dried.
[0141] The resulting PEG-COOH was dissolved in 8.6 × 10 -5mol and α-cyclodextrin at 1.2 × 10 -2 mol was dissolved in 100 mL of pure water and allowed to stand in a freezer overnight. The resulting white paste-like compound was then freeze-dried to obtain a powdered inclusion complex.
[0142] The following materials were dissolved in 100 mL of anhydrous dimethylformamide and reacted at 4° C. for 24 hours. Obtained inclusion complex: 14 g Adamantaneamine 1.1×10 -3 Mol Benzotriazol-1-yloxy-tris(dimethylamino)phosphonium salt 1.1×10 -3 Mol Ethylisopropylamine 1.2×10 -3 Mol The product was then washed twice with a dimethylformamide / methanol solution (1:1, v / v) and twice with methanol. It was then washed with a mixed solution of 80 mL of anhydrous dimethyl sulfoxide and 800 mL of pure water, and freeze-dried to obtain polyrotaxane A10 in which α-cyclodextrin was encapsulated. The composition and physical properties are shown in Table 1.
[0143] [Table 1]
[0144] The abbreviations in Table 1 are as follows: PEG: Polyethylene glycol α-CD: α-cyclodextrin MMA / St: Methyl methacrylate / styrene polymer structure MA / St: Methyl acrylate / styrene polymer structure CL: Polycaprolactone structure The weight average molecular weight in Table 1 was measured by the method described above.
[0145] <Production example of magnetic carrier core 1> Process 1 (weighing and mixing process) Fe2O368.3% by mass MnCO328.5% by mass Mg(OH)22.0% by mass SrCO31.2% by mass The above ferrite raw material was weighed, 80 parts of the ferrite raw material was mixed with 20 parts of water, and then wet-mixed in a ball mill using zirconia having a diameter (φ) of 10 mm for 3 hours to prepare a slurry. The solid content of the slurry was 80 mass %.
[0146] Step 2 (pre-firing step) The mixed slurry was dried using a spray dryer (manufactured by Okawara Kakoki Co., Ltd.) and then fired in a batch-type electric furnace in a nitrogen atmosphere (oxygen concentration 1.0% by volume) at a temperature of 1050° C. for 3.0 hours to produce calcined ferrite.
[0147] Process 3 (Crushing process) The calcined ferrite was crushed to about 0.5 mm using a crusher, and water was added to prepare a slurry. The solid content of the slurry was set to 70 mass %. The slurry was crushed for 3 hours using a wet ball mill with 1 / 8 inch stainless steel beads to obtain a slurry. The slurry was further crushed for 4 hours using a wet bead mill with 1 mm diameter zirconia to obtain a calcined ferrite slurry with a volume-based 50% particle size (D50) of 1.3 μm.
[0148] Process 4 (granulation process) To 100 parts of the calcined ferrite slurry, 1.0 part of ammonium polycarboxylate as a dispersant and 1.5 parts of polyvinyl alcohol as a binder were added, and the mixture was granulated into spherical particles using a spray dryer (manufactured by Okawara Kakoki Co., Ltd.) and dried. The resulting granulated material was subjected to particle size adjustment, and then heated at 700°C for 2 hours using a rotary electric furnace to remove organic substances such as the dispersant and binder.
[0149] Step 5 (baking step) The material was fired in a nitrogen atmosphere (oxygen concentration 1.0% by volume) for 2 hours from room temperature to the firing temperature (1100°C), and then held at 1100°C for 4 hours. The material was then cooled to 60°C over 8 hours, returned from the nitrogen atmosphere to the air, and taken out at a temperature of 40°C or less.
[0150] Step 6 (sorting step) After the aggregated particles were crushed, the particles were sieved through a sieve with 150 μm openings to remove coarse particles, air classification to remove fine powder, and magnetic separation to remove low magnetic particles to obtain porous magnetic particles 1. The volume average particle size of the porous magnetic particles 1 was 41 μm, the pore diameter was 0.45 μm, and the pore volume was 45 mm 3 The pore size and pore volume were measured by the methods described above.
[0151] Process 7 (filling process) Methyl silicone resin (product name: KR-251, Shin-Etsu Chemical Co., Ltd.), polyrotaxane A1, and γ-aminopropyltrimethoxysilane as an additive were placed in a container in the amounts shown in Table 2. Then, the resin was dissolved in toluene to obtain a solid content of 20 mass %, to obtain a filled resin solution. 100 parts of porous magnetic particles 1 were placed in a stirring vessel of a mixer (a universal stirrer NDMV type manufactured by Dalton Co., Ltd.), and the temperature was kept at 60°C. At normal pressure, the filled resin solution was added dropwise to obtain a solid content of 5.26 mass parts.
[0152] After the dropwise addition was completed, stirring was continued while adjusting the time, and the temperature was raised to 70° C. to fill the porous magnetic core particles with the filling resin.
[0153] After cooling, the resin-filled magnetic core particles obtained were transferred to a mixer (UD-AT type drum mixer manufactured by Sugiyama Heavy Industries Co., Ltd.) equipped with a spiral blade in a rotatable mixing container, and the temperature was raised to 140°C at a heating rate of 2°C / min under a nitrogen atmosphere while stirring. Heating and stirring were then continued at 140°C for 50 minutes to harden the filling resin in the porous magnetic core particles.
[0154] After that, it was cooled to room temperature, and the core particles filled with the resin and hardened were taken out, and non-magnetic materials were removed using a magnetic separator. Furthermore, coarse particles were removed using a vibrating sieve to obtain magnetic carrier cores 1 filled with the resin. The added parts and content ratios are shown in Table 2.
[0155] <Production Examples of Magnetic Carrier Cores 2 to 23> Magnetic carrier cores 2 to 23 were obtained in the same manner as in the production example of magnetic carrier core 1, except that the materials used and the amounts added were changed as shown in Table 2.
[0156] [Table 2]
[0157] <Example 1> <Magnetic Carrier 1 Manufacturing Example> Magnetic carrier core 1 100.0 parts Coating resin 1 2.0 parts First, the above-mentioned parts of coating resin 1 were diluted with toluene so that the resin content was 5%, and a resin solution was prepared by thoroughly stirring. Then, 100.0 parts of magnetic carrier core 1 was placed in a planetary motion mixer (Nauta Mixer VN type manufactured by Hosokawa Micron Corporation) maintained at a temperature of 60°C, and the above-mentioned resin solution was added. As a method of addition, 1 / 2 the amount of resin solution was added, and the solvent was removed and the coating operation was performed for 30 minutes. Next, another 1 / 2 the amount of resin solution was added, and the solvent was removed and the coating operation was performed for 40 minutes.
[0158] The magnetic carrier coated with the coating resin was then transferred to a mixer (UD-AT type drum mixer manufactured by Sugiyama Heavy Industries Co., Ltd.) equipped with a spiral blade in a rotatable mixing container, and heat-treated for 2 hours at a temperature of 120°C in a nitrogen atmosphere while stirring at 10 revolutions per minute. The magnetic carrier obtained was separated into low magnetic particles by magnetic separation, passed through a sieve with 150 μm openings, and then classified with an air classifier to obtain magnetic carrier 1.
[0159] <Example of manufacturing two-component developer> Using toner 1 and magnetic carrier 1, each material was shaken in a shaker (YS-8D type: manufactured by Yayoi Co., Ltd.) so that the toner concentration was 8% by mass, to obtain a two-component developer. The vibration condition of the shaker was 200 rpm and 2 minutes.
[0160] <Example of manufacturing replenishment developer> 92 parts of toner 1 was added to 8 parts of magnetic carrier 1, and mixed for 5 minutes in a V-type mixer in an environment of normal temperature and humidity of 23° C. / 50% RH to obtain a replenishment developer.
[0161] <Evaluation> The image forming apparatus used was a modified color copier (product name: imagePRESS C850, manufactured by Canon) with the following modifications: The development contrast can now be adjusted to any value, and the automatic correction by the device has been disabled. The AC component of the developing bias was modified to have a frequency of 2.0 kHz, and the peak-to-peak voltage (Vpp) was modified so that it could be changed in 0.1 kV increments from 0.7 kV to 1.8 kV. Modified to enable monochrome image formation.
[0162] When forming an image, the developer contained in the cyan developing device was replaced with the above-mentioned two-component developer, and the developer contained in the cyan replenishment developer container was replaced with the above-mentioned replenishment developer.
[0163] Using the modified machine, laser beam printer paper CS-814 (81.4 g / m 2 ) (available from Canon Marketing Japan Inc.), a cyan monochrome image was formed, and the following evaluation tests were carried out.
[0164] (Evaluation 1) Evaluation of image density change In a N / L environment (temperature 23°C / humidity 5RH%), a solid image of 15 mm x 15 mm in size was printed on transfer paper (CS-814) (toner load on paper: 0.35 mg / cm 2) was formed in a total of nine locations at the center and edge of the paper, and an evaluation image was output. The density of the center of each image was measured using an X-Rite color reflection densitometer (Color reflection densitometer X-Rite 404A) to obtain the average value of the obtained image density. Next, in the same environment, 5000 sheets of solid images with a print ratio of 1% were output, and 5000 sheets of solid images with a print ratio of 40% were output, and this was repeated for a total of 50,000 sheets of paper passing, and then 5000 sheets of solid images with a print ratio of 1% were output. The same evaluation image as before the output was output, and the average value of the obtained image density was obtained. The difference between the average value of the density obtained before the durability test and the average value of the density obtained after the durability test was calculated. The results are shown in Table 4. It was determined that the effect of the present disclosure was obtained when the difference in the average value was 0.15 or less. In addition, the above-mentioned cumulative image output of 50,000 sheets is assumed to be a case in which a user continues to output images for a long time.
[0165] (Evaluation 2) Evaluation of density changes at various image densities At the start of the above test (1), the developing bias was adjusted, and an evaluation image having an image band set to the density of each pattern shown below was output. Then, the above test (1) was performed, and thereafter, a similar evaluation image was output with the same developing bias, and the image density of each image band was measured. The measured value was evaluated based on the number of patterns whose image density range was outside the image density range of the initially set pattern. It was determined that the effect of the present disclosure was obtained when the number of patterns that were out of the range was 5 or less.
[0166] The image density was measured using an X-Rite color reflection densitometer (X-Rite 404A). The evaluation results are shown in Table 4. Pattern 1: Image density 0.10 to 0.13 Pattern 2: Image density 0.25 to 0.28 Pattern 3: Image density 0.40 to 0.43 Pattern 4: Image density 0.55 to 0.58 Pattern 5: Image density 0.70 to 0.73 Pattern 6: Image density 0.85 to 0.88 Pattern 7: Image density 1.00 to 1.03 Pattern 8: Image density 1.15 to 1.18 Pattern 9: Image density 1.30 to 1.33 Pattern 10: Image density 1.45 to 1.48
[0167] (Rating 3) Normal durability rating In addition to the above conditions, evaluation was also performed under the following conditions.
[0168] (Rating 3-1:N / L environment) The evaluation was performed in the same manner as in (Evaluation 1) and (Evaluation 2) above, except that the cumulative image output of 50,000 sheets was changed to the output of 20,000 solid images with a print ratio of 1%. The evaluation results are shown in Table 4.
[0169] (Rating 3-2:N / N environment) In addition, the N / L environment was changed to an N / N environment (temperature 23°C / humidity 50%RH), and the cumulative image output of 50,000 sheets was changed to the output of 20,000 solid images with a print ratio of 1%, but the same operations as those in (Evaluation 1) and (Evaluation 2) were performed and evaluation was performed. The evaluation results are shown in Table 4.
[0170] <Examples 2 to 26 and Comparative Example 1> Magnetic carriers 2 to 27 were produced and evaluated in the same manner as in Example 1, except that the type of magnetic carrier core and the amount of coating resin were changed as shown in Table 3. The evaluation results are shown in Table 4.
[0171] [Table 3]
[0172] [Table 4]
Claims
1. A magnetic carrier having a magnetic carrier core particle and a surface layer covering the surface of the magnetic carrier core particle, The magnetic carrier core particles have a resin present in at least a part of the voids of the porous magnetic particles, The resin includes a first resin and a second resin different from the first resin, the first resin is a polyrotaxane; The polyrotaxane is (i) a plurality of cyclic molecules; (ii) a chain molecule that is pierced and included in the ring of the cyclic molecule; having (iii) the chain molecule has two or more blocking groups that prevent the cyclic molecule from being detached from the chain molecule; A magnetic carrier comprising:
2. 2. The magnetic carrier according to claim 1, wherein the cyclic molecule is a molecule having a cyclodextrin skeleton.
3. 3. The magnetic carrier according to claim 2, wherein the molecule having a cyclodextrin skeleton has a weight average molecular weight of 2,500 to 50,000.
4. The molecule having a cyclodextrin skeleton has a cyclodextrin and a side chain attached to the cyclodextrin. The magnetic carrier according to claim 2 or 3.
5. The side chain has a polyester structure, a vinyl polymer structure, a polyurethane structure, a polyurea structure, or a polyether structure. The magnetic carrier according to claim 4.
6. the side chain has a polyester structure, 6. The magnetic carrier according to claim 4, wherein the polyester structure is a polycaprolactone structure.
7. the polyrotaxane comprises a first polyrotaxane and a second polyrotaxane, the polyrotaxane includes a bound polyrotaxane formed by binding the first polyrotaxane and the second polyrotaxane, The first polyrotaxane and the second polyrotaxane are bonded to each other by forming a chemical bond between a cyclic molecule of the first polyrotaxane and a cyclic molecule of the second polyrotaxane. The magnetic carrier according to any one of claims 1 to 6.
8. 8. The magnetic carrier according to claim 1, wherein the chain molecule is a molecule having a polyalkylene glycol chain.
9. 9. The magnetic carrier according to claim 1, wherein the content of the resin relative to the porous magnetic particles is 2.0% by mass or more and 15.0% by mass or less.
10. 10. The magnetic carrier according to claim 1, wherein the content of the first resin in the resin is 1.0% by mass or more and 30.0% by mass or less.
11. 11. The magnetic carrier according to claim 1, wherein the surface layer is a resin layer.
12. A two-component developer containing a toner and a magnetic carrier, The magnetic carrier is the magnetic carrier according to any one of claims 1 to 11. A two-component developer.
13. A replenishment developer containing a toner and a magnetic carrier, The magnetic carrier is the magnetic carrier according to any one of claims 1 to 11. A replenishing developer comprising:
14. A method for producing the magnetic carrier according to any one of claims 1 to 11, a step of filling the voids in the porous magnetic particles with a mixture of the first resin and a raw material for the second resin;
Citation Information
Patent Citations
Electrostatic charge image developer
JP1995064344A
Electrophotographic photoreceptor, image forming apparatus using the same, process cartridge and image forming method
JP2011248288A
Electrophotographic photoreceptor and image forming device using the same
JP2012181244A
Magnetic carrier and two-component developer
JP2014006513A
Electrophotographic member
JP2014066857A